Experimental constraints on the stability and oscillation of water vapor film—a precursor for phreatomagmatic and explosive submarine eruptions - Sonder, Ingo; Moitra, Pranabendu (Frontiers in Earth Science, 2022)
Pre-mixing of magma and external water plays a key role in driving explosive phreatomagmatic and submarine volcanic eruptions. A thin film of water vapor forms at the magma-water interface as soon as hot magma comes in direct contact with the cold water (Leidenfrost Effect). The presence of a stable vapor film drives efficient mixing and mingling between magma and water, as well as magma and wet and water saturated sediments. Such mixing occurs before explosive molten fuel-coolant type interactions. Using high-temperature laboratory experiments, we investigate the effect of magma and water temperatures on the stability of vapor film. The experiments were performed with re-melted volcanic rock material, from which spherically-shaped rock samples were produced. These samples were heated to 1100°C and then submerged in a water pool with a constant temperature (3–93°C). The experiments were recorded on video, and, synchronously, sample and water temperatures were measured using thermocouples. Time-dependent thickness of the vapor film was measured from the video material. The vapor film tends to oscillate with time on the order of 100 Hz. We find that the vertical collapse rates along the sample-water interfaces are 13.7 mm/s and and 4.2 mm/s for water temperature of 3.0°C and 65°C, respectively. For a given initial sample temperature, the thickness and stability time scales decrease with decreasing water temperature, which has implications for the efficiency of pre-mixing required for explosive eruptions. Using thermodynamics and previously measured material parameters it is shown that a sudden collapse of the vapor film can start brittle fragmentation if the melt, and thus serve as start point of thermo-hydraulic explosions.